2013
DOI: 10.1038/tp.2013.77
|View full text |Cite
|
Sign up to set email alerts
|

Opposing actions of environmental enrichment and Alzheimer’s disease on the expression of hippocampal microRNAs in mouse models

Abstract: Alzheimer's disease (AD) is the most common form of dementia in the elderly. Although there are no drugs that modify the disease process, exposure to an enriched environment (EE) can slow the disease progression. Here, we characterize the effects of AD and EE on the post-transcriptional regulators, microRNAs (miRNAs), which may contribute to the detrimental and beneficial effects of AD and EE, respectively, on synaptic plasticity-related proteins and AD pathology. We found for the first time miRNAs that were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 114 publications
(151 reference statements)
3
45
0
Order By: Relevance
“…Tomosyn emerges as an important regulator of both basal synaptic transmission and presynaptic forms of plasticity. In support of this role in vivo is the recent observation that tomosyn levels are down-regulated in animals exposed to enriched environment and up-regulated in an Alzheimer's disease mouse model (Barak et al, 2013b). …”
Section: Discussionmentioning
confidence: 96%
“…Tomosyn emerges as an important regulator of both basal synaptic transmission and presynaptic forms of plasticity. In support of this role in vivo is the recent observation that tomosyn levels are down-regulated in animals exposed to enriched environment and up-regulated in an Alzheimer's disease mouse model (Barak et al, 2013b). …”
Section: Discussionmentioning
confidence: 96%
“…MiR-124a showed a similar performance following enriched environment condition [175]. MiR-325 was downregulated in 3 × Tg AD mice but upregulated by EE, which may open new avenues for the studies of treating AD [176]. Until now, this field of exploration is now relatively new, therefore many questions regarding the epigenetic impacts of EE remain unsolved.…”
Section: What Are the Mechanisms For The Effect Of Cognitive Activity?mentioning
confidence: 99%
“…For example, Serpente et al (2011) found that miR-369 may affect the occurrence and development of AD via the LDL receptor 1 gene (OLR1, rs1050283). Barak et al (2013) found decreased levels of miR-369 in the hippocampal tissue of the 3xTg-AD mouse brain. Our preliminary experiment also showed a similar phenomenon in 6-month-old 3xTg-AD mice (see Supplementary Figure S1).…”
Section: Introductionmentioning
confidence: 81%